(untitled) (International Journal of Engineering and Computer Science, 2017)
As we all know, Wireless Local Area Networks (WLANs), which is based on the IEEE 802.11 standards, is growing at a very considerable rate in the fields of business, schools and other organizations. As WLAN deployments increase, so does the challenge to provide these networks with security. Security can be needed either for the technical issues in the mechanisms, or due to software implementations. This survey paper proposes the use of GSE technique to analyze the shortcomings in the standards specified. After providing with the issues, we will switch focus to the Robust Security Network (RSN) which is proposed in the IEEE 802.11i standard using different GSE models.